Russia-Ukraine War and Implications of Finland’s Membership of NATO - Ngelale, Stephanie (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This study examines how the war between Russia and Ukraine has tilted Finland into the orbit of NATO. Therefore, the research approach is a qualitative systematic literature review, and it examines scholarly papers, foreign policy reports, and websites like Carnegie Europe and the Atlantic Council that deal with international relations. In addition, the study examines what this milestone poses for East-West relations within the international system going-forward. The study as a concluding remark indicated that the war between Russia and Ukraine has significant geo-political ramifications which are discussed in this study. Likewise, Ukraine's struggles on the battlefields are still raging, while neighbouring nations like Finland and Sweden have sought stronger ties with both of them making connections with NATO for increased security in response to the crisis. Similarly, the defection of Finland into the NATO alliance is of consequential impact on global dynamics. As a result, insightful information on the changing dynamics of the area and the difficulties of post-conflict international cooperation and security are gleaned from the comprehensive literature research.